Forms of Instagram Social Media Communication in Promoting Lampung Province Tourism - Rosy Febriani Daud; Deddy Apriliani; Ade Rama Dhani Kusuma (CHANNEL: Jurnal Komunikasi, 2021)
This study aimed to determine the forms of promotion on social media by the tourism office in Lampung Province. The study is trying to find out the obstacles experienced by the Lampung Province tourism office in promoting tourism in Lampung Province, to determine the level of success of the tourism office in conducting tourism promotion using Instagram. The method used in this research is the descriptive qualitative method. This qualitative research is descriptive, using secondary data as a reference. Secondary data collection techniques are carried out using literature study techniques, including using literature data in journals, books, articles, and news related to research. The research results found by researchers were a form of promotion in the form of advertising, sale promotion, publicity, promotion through social media, especially Instagram, which is effective in stimulating attention. However, Instagram is still not practical at the stages of interest (interest), desire (desire), and action ( action). Promotion through Instagram creates trust for consumers because there are many valuable testimonials and comments for users to find out more information. Images with HD features look attractive, and the captions accompanying images or video posts also add to the appeal. The obstacles are external and internal. The level of success, seen from the large number of tourists who come and can be seen from how many likes the community gives, or how many impressions the community leaves and the many followers on the account, the success rate of promotion using social media is flourishing.